Inside the genome: understanding genetic influences on oxidative stress - Krishnamurthy, Hari Krishnan; Rajavelu, Imbaasree; Pereira, Michelle; Jayaraman, Vasanth; Krishna, Karthik; Wang, Tianhao; Bei, Kang; Rajasekaran, John J. (Frontiers in Genetics, 2024)
Genetics is a key factor that governs the susceptibility to oxidative stress. In the body, oxidative burden is regulated by the balance between the prooxidant genes that orchestrate processes that produce oxidant species, while the antioxidant genes aid those involved in scavenging these species. Together, the two components aid in maintaining the oxidative balance in the body.Genetic variations can influence the expression and activity of the encoded proteins which can then affect their efficiency in regulating redox processes, thereby increasing the risk of oxidative stress. This review studies single nucleotide polymorphisms (SNPs) that bear relevance to oxidative stress by exploring the variations in the prooxidant genes, such as XDH, CYBA, CYP1A1, PTGS2, NOS, and MAO and antioxidant genes including SOD, CAT, GPX, GSS, GLUL, GSR, GSTM1, GSTM5, GSTP1, TXN and HMOX1. Early identification of individuals at the increased risk of oxidative stress is possible from the assessment of sequence of these genes. Integrating genetic insights into oxidative stress management measures can pave the way for personalized medicine that tailors' healthcare approaches to individual genetic profiles. Effective genetic assessment along with routine quantification of biological markers can improve and monitor treatment strategies, enhancing mitigation approaches that maintain cellular health and promote longevity.